Gold immunochromatographic assay for trimethoprim in milk and honey samples based on a heterogenous monoclonal antibody. Issue 6 (2nd November 2017) - Chen, Yanni; Liu, Liqiang; Xie, Zhengjun; Zhu, Jianping; Song, Shanshan; Kuang, Hua
ABSTRACT: Three heterogenous haptens (3, 4, 5-Trimethoxybenzoic acid [H1], 3, 4, 5-Trimethoxyphenylacetic acid [H2], 3-(3, 4, 5-Trimethoxyphenyl) propanoic acid [H3]) were used to synthesize immunogens, with the aim of screening a more sensitive monoclonal antibody (mAb) for trimethoprim (TMP). H2 proved to be the best heterogenous hapten. The mAb was specific with no cross-reactivity with other structurally related chemicals. The 50% maximal inhibitory concentration of the mAb against TMP was 1.98 µg L −1, which is more sensitive compared with the mAb reported in our previous work. A mAb-based gold immunochromatographic assay (GICA) was established to analyze TMP residues in milk and honey samples. The concentration of coating antigen in test line and concentration of mAb conjugated with gold nanoparticles was 0.3 µg mL −1 and 0.25 µg mL −1, respectively. Under optimized conditions, the visual limit of detection concentration of TMP spiked in milk and honey samples was 10 µg L −1 and 15 µg kg −1, respectively. The proposed GICA provides rapid and simple determination of TMP residues in milk and honey samples.